Discussing alcohol in medicines use reviews: experiences of patients in a community pharmacy context. (15th November 2018) - Jamie, Kimberly; Oliver, Emily J; Paterson, Alistair; Whittlesea, Cate
Abstract: Objectives: Although pharmacist-led medicines use reviews (MURs) are effective for medicines management, little is understood about patients' experiences of alcohol-related advice delivered therein. Sampling a population at high risk for misuse (within an area of socio-economic deprivation), we explored patient experiences of alcohol-related MURs. Methods: Two focus groups were conducted with patients who had discussed alcohol in an MUR in the preceding 3 months ( n = 9). Data were analysed thematically. Key findings and conclusion: Patients were open to discussing alcohol in the MUR context. The absence of practitioner-patient power asymmetry and pharmacists' sensitivity to cultural contexts were critical to patient engagement.